Chronology of the Pleistocene deposits at Elands Bay Cave (South Africa) based on charcoals, burnt lithics, and sedimentary quartz and feldspar grains - Tribolo, C.; Mercier, N.; Valladas, H.; Lefrais, Y.; Miller, C. E.; Parkington, J. E.; Porraz, G. (Southern African Humanities, 2016)
In 2011 we conducted a field campaign at the site of Elands Bay Cave (EBC), on the West coast of South Africa, with the aim of clarifying the nature and chronology of its human Pleistocene occupations. In the present paper, we present the results of a chronology based on various materials and methods: radiocarbon (C14) dating was applied to 8 fragments of charcoal whereas luminescence dating methods (OSL, IRSL and TL) were applied to quartz and feldspar grains extracted from 5 sediment samples and to 4 burnt fragments of quartzite rock. For the upper part of the sequence, the luminescence ages are either in agreement with or slightly younger than the C14 ages. The results suggest that the upper part of the EBC sequence extends from MIS3 to MIS2, including successively late Middle Stone Age (starting from 38 ± 3 ka), Early Later Stone Age (ending 22 ka ago) and Robberg occupations (starting 19.1 ± 0.3 ka ago). The lower part of the EBC sequence, associated with Early Middle Stone Age assemblages, remains poorly constrained: the sediment sample taken above could be a mixture of different layers and could not be dated, whereas OSL ages for sediments below are 236 ± 23 ka and only one stone sample could be dated within this layer (83 ± 14 ka). Considering both the chronological and techno-cultural points of view, the EBC sequence is complementary to the Diepkloof sequence, located less than 20 km eastward.